A mixed-method outcome evaluation of a specialist Alcohol Hospital Liaison Team. (November 2016) - McGeechan, Grant J; Wilkinson, Kirsty G; Martin, Neil; Wilson, Lynn; O'Neill, Gillian; Newbury-Birch, Dorothy
Aims: To evaluate the effectiveness of an Alcohol Hospital Liaison Team at reducing alcohol-specific hospital attendances and admissions. Methods: In a mixed-method evaluation, 96 patients who accessed the team were monitored using data for alcohol-specific hospital attendances and Accident and Emergency (A&E) admissions before, during, and after engaging with the team. A feedback survey was sent to patients and a focus group was held with staff from the team to identify barriers and facilitators to the successful delivery of this service. Results: No differences were observed when looking at alcohol admissions or A&E attendances before patients engaged with the service to those after discharge. While hospital admissions decreased slightly and A&E attendances increased slightly, these differences were not significant. Hospital admissions and A&E attendances increased significantly during engagement with the service. The focus group identified confusion over who should be delivering brief interventions and that the team was holding onto patients for too long. Conclusion: The results of this evaluation demonstrated that this team was not effective at reducing alcohol attendances or admissions due to a number of factors. Policy makers should make note of the barriers to effectiveness highlighted in this article, before commissioning alcohol care teams in the future.